The Correlation of EMMPRIN and EGFR Overexpression toward Muscle Invasiveness in Urothelial Carcinoma of Bladder - Leonita Agustin Hambalie; Anny Setijo Rahaju; Gondo Mastutik (Indian Journal of Forensic Medicine & Toxicology, 2021)
Urothelial carcinomas represent 90% of all primary bladder cancers. Muscle invasion is a critical prognosticdeterminant in urothelial carcinoma. The overexpression of EMMPRIN and EGFR was found in urothelialcarcinoma. The association between the two markers has not been reported in urothelial carcinoma,therefore we aimed to analyze the expression of EMMPRIN and EGFR and investigate their association withurothelial carcinoma invasiveness. Paraffin-embedded tissues were obtained from 54 urothelial carcinomapatients which then underwent immunohistochemistry staining for EMMPRIN and EGFR antibody. Thecomparison of EMMPRIN and EGFR expression was tested using the Mann Whitney U test. The correlationwas analyzed using the Spearman test. Results showed a significant difference of EMMPRIN expressionbetween non-muscle-invasive and muscle-invasive bladder cancer (p = 0.000), and EMMPRIN expressionwas significantly correlated with the muscle invasion (rs = 0.481, p = 0.000). A significant difference ofEGFR expression between the non-muscle-invasive and muscle-invasive bladder cancer was also found(p = 0.020), and EGFR expression was significantly correlated with the muscle invasion (rs = 0.319, p =0.019). The expression of EMMPRIN was positively correlated with EGFR in urothelial carcinoma (rs =0.322, p = 0.018). The expression of EMMPRIN and EGFR are two potential biomarkers for urothelialcarcinoma invasiveness which may be helpful to differentiate between muscle-invasive and non-muscleinvasive bladder cancer.